Cerium ion doped high-entropy fluoride scintillation crystal and preparation method and application thereof

By doping cerium ions into the scintillator of LaGdCaSrBaF12 high-entropy substrate, Ce:LaGdCaSrBaF12 high-entropy fluoride scintillation crystal is formed, which solves the problem of unoptimized scintillation performance and attenuation time characteristics in a high-entropy environment, and achieves excellent photoluminescence performance and radiation resistance.

CN119710926AActive Publication Date: 2025-03-28TONGJI UNIV

Patent Information

Application Number
CN202411608118.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-12
Publication Date
2025-03-28
Estimated Expiration
2044-11-12

AI Technical Summary

Technical Problem

In the environment of strong lattice distortion caused by high entropy, the scintillator's scintillator's scintillator's scintillator's scintillator's scintillator has not been fully understood and optimized.

Method used

By doping cerium ions into the scintillator of LaGdCaSrBaF12 high-entropy substrate, Ce:LaGdCaSrBaF12 high-entropy fluoride scintillation crystal is formed, and the energy transfer efficiency of self-destructive excitons is improved by using the high-lattice distortion environment provided by the high-entropy matrix, and the radiation hardness of the material is enhanced through the hysteresis diffusion effect.

Benefits of technology

The excellent photoluminescence performance and short scintillation time of high entropy fluoride scintillation crystal are achieved, which enhances the radiation resistance and chemical stability of the material and extends the benefit life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119710926A_ABST
    Figure CN119710926A_ABST
Patent Text Reader

Abstract

The invention relates to a cerium ion doped high-entropy fluoride scintillation crystal and a preparation method and application thereof. The preparation method comprises the following steps: taking single crystal particles or powder of LaF3, GdF3, CaF2, SrF2, BaF2 and CeF3 as raw materials, doping Ce ions, uniformly grinding to obtain a matrix material, vacuumizing, carrying out high-temperature sintering, ensuring that the matrix material is completely melted and impurities are removed, slowly cooling, carrying out crystal growth, and cooling to room temperature to obtain the cerium ion doped high-entropy fluoride scintillation crystal. The chemical formula of the high-entropy fluoride scintillation crystal is Ce: M1M2CaSrBaF12, wherein M1 and M2 are any two of Y, Lu, Gd, La, Lu, Sc and Ce. Compared with the prior art, the LaGdCaSrBaF12 high-entropy crystal prepared by the invention has lower phonon energy and smaller 5d energy level cleavage, and can greatly reduce the non-radiative transition probability of the 5d energy level of Ce < 3 + > ions. In addition, the disorderly distributed mixed crystal also regulates and controls the local coordination structure of Ce < 3 + > ions on the scales of atoms, molecules and groups, so that true disorder is achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of crystal materials, and in particular to a cerium ion-doped high-entropy fluoride scintillation crystal and a preparation method and application thereof. Background Art

[0002] Scintillator is a material that can convert high-energy radiation into visible light. It is widely used in high-energy physics detection, nuclear medicine imaging, security inspection equipment and other fields. The core principle is that when high-energy particles (such as X-rays or gamma rays) irradiate the scintillator material, the electrons in the inner layer of the scintillator are excited to become free electrons, and the inner electrons further scatter and excite Auger electrons. Through thermal effects, free electrons and free holes gather at the top of the valence band and the bottom of the conduction band of the material. Finally, when the free electrons and holes return to the ground state, they release energy in the form of photons. The light generated by this process is called scintillation light. The performance of the scintillator determines the intensity, stability and response speed of the light output. In 1903, William Crookes published the first use of ZnS scintillator to count alpha particles. By the end of the twentieth century, EDBourret-Courchesne and SEDerenzo et al. conducted in-depth research on the performance and growth process of cerium-doped materials such as alkaline earth halides. These studies showed that the optical properties of these scintillators can be significantly improved by optimizing the doping concentration and improving the crystal growth technology.

[0003] Cerium ions (Ce3+) are a commonly used scintillation center. They are widely used in scintillators because of their fast luminescence response time and high photon yield in the 4f→5d transition. Especially in oxide and fluoride matrix materials, the doping of cerium ions can significantly improve the photoluminescence performance of scintillators while maintaining the high mechanical strength and chemical stability of the materials. In addition, cerium-doped scintillator materials usually have a shorter scintillation decay time, which is crucial for detection applications requiring high time resolution. The 5d energy level of cerium ions is greatly affected by the crystal field, while the weak field environment of fluoride makes the 5d energy level splitting not serious, and the probability of non-radiative transition within the 5d energy level is small. In 2007, G. Bizarri and P. Dorenbos explained in detail the energy transfer process from self-trapped excitons to cerium ions in cerium-doped alkaline earth halides and the influence of the entire scintillation decay process in cerium-doped lanthanum bromide crystal materials. Up to now, the crystal growth method, material types and characterization methods of cerium-doped alkaline earth halides have undergone a long period of development and achieved great results. However, the scintillation performance of scintillators in the environment of strong lattice distortion caused by high entropy remains unknown.

[0004] High entropy materials are a new type of multi-component alloys or compounds that have emerged in recent years. They are usually composed of five or more elements in a nearly equimolar ratio. Compared with traditional single or two-component materials, high entropy materials present more complex and unique characteristics in chemical composition, atomic arrangement and physical properties. Such materials usually exhibit excellent mechanical properties, thermal stability and corrosion resistance, and therefore have received widespread attention in the field of structural materials.

[0005] With the deepening of research, the concept of high entropy materials has gradually expanded from metal alloys to functional materials such as ceramics, oxides, and fluorides. In the field of scintillators, the introduction of high entropy materials has many potential advantages. First, the lattice distortion brought about by the high entropy effect helps to improve the energy resolution and light yield of scintillator materials, because the mixing of different atomic sizes may enhance the localization effect of the excited state, thereby improving the luminescence efficiency. Secondly, the diversity of elements in high entropy materials provides a wealth of doping options, which can optimize the luminescence spectrum and response speed of the scintillator. For example, by introducing different rare earth elements into the fluoride matrix, luminescence regulation in a broadband or specific wavelength range can be achieved to meet different application requirements.

[0006] In Ce-doped LaGdCaSrBaF 12 In high-entropy base scintillators, the material is composed of more than five alkaline earth metals and rare earth metals, forming a highly complex crystal structure. The uniqueness of high-entropy materials lies in the fact that they have multiple elements with different valence states, which form complex interactions with each other. This structure not only gives the material stronger radiation resistance and chemical stability, but also can effectively suppress defect states in the crystal, reduce non-radiative transition processes, and improve photoluminescence efficiency.

[0007] Cerium doped LaGdCaSrBaF 12 The high-entropy substrate scintillator exhibits excellent photoluminescence properties, indicating that the material can produce strong visible light after excitation. This shows that under the influence of the high-entropy substrate, the excited state carriers effectively participate in photon emission. At the same time, the photoluminescence decay time of the material reaches an extremely excellent 5.74ns (82.9%). However, although the photoluminescence performance is good, the characteristics of the scintillation decay time have not been tested. The decay time is an important parameter for evaluating the response speed of the scintillator and is usually related to the excited state lifetime of the doped ions in the material. The complex lattice environment of the high-entropy material may have an impact on the decay time, which deserves further testing and analysis in subsequent studies. Summary of the invention

[0008] The purpose of the present invention is to overcome the defects of the above-mentioned prior art and provide a cerium ion doped high entropy fluoride scintillation crystal and its preparation method and application. 12The high lattice distortion environment provided by the high entropy matrix in the high entropy crystal provides more energy wells for the formation of self-trapped excitons, making the energy transfer efficiency of self-trapped excitons to the luminescence center higher and the material scintillation performance better. The hysteresis diffusion effect caused by high entropy increases the radiation hardness of the material and can enhance the service life of the material.

[0009] The purpose of the present invention can be achieved by the following technical solutions:

[0010] The present invention provides a cerium ion doped high entropy fluoride scintillation crystal, the chemical formula of the scintillation crystal is Ce:M1M2CaSrBaF 12 , where M1 and M2 are any two of Y, Lu, Gd, La, Lu, Sc, and Ce;

[0011] The space group of the scintillation crystal is Fm-3m (225), which belongs to the cubic crystal system.

[0012] Furthermore, the chemical formula of the scintillation crystal is Ce:LaGdCaSrBaF 12 .

[0013] The present invention also provides a method for preparing a cerium ion-doped high-entropy fluoride scintillation crystal, comprising the following steps:

[0014] S1: Using single crystal particles or powders of LaF3, GdF3, CaF2, SrF2, BaF2 and CeF3 as raw materials, doping them with Ce ions, and grinding them evenly to obtain the matrix material;

[0015] S2: The matrix material in S1 is loaded into a porous graphite crucible, and a lid is put on the crucible to prevent the large amount of volatilization of the raw materials, and the crucible is placed in a hot field and evacuated;

[0016] S3: After the vacuum is evacuated, the power is turned on to increase the temperature and keep it warm for a period of time to ensure that the matrix material in S1 is completely melted and impurities are removed, and then the temperature is slowly lowered to grow the crystal. After the growth is completed, the temperature is lowered to room temperature to obtain a cerium-doped high-entropy fluoride scintillation crystal.

[0017] Furthermore, in S1, the purity of the single crystal particles or powders of LaF3, GdF3, CaF2, SrF2, BaF2 and CeF3 is 5N.

[0018] Further, in S1, the grinding time is 40-60 min;

[0019] In S1, the doping molar mass ratio of the Ce ions is 0.5%-3.0%.

[0020] Furthermore, in S1, 1 wt. % of PbF2 is added to the matrix material, and the PbF2 is used as a deoxidizer to prevent the fluoride raw material from being oxidized.

[0021] Furthermore, in S2, the vacuum is drawn to below 8 Pa.

[0022] Furthermore, in S3, the heating rate is 100-200°C / h, the temperature is raised to 1350-1400°C, and the constant temperature time is 8-12h.

[0023] Further, in S3, the slow cooling rate is 1.5°C / h;

[0024] In S3, the growth is terminated by slowly cooling the temperature to 150°C and then to room temperature at a cooling rate of 30-50°C / h.

[0025] The present invention also provides an application of a cerium ion-doped high-entropy fluoride scintillation crystal. The cerium ion-doped high-entropy fluoride scintillation crystal is used in the preparation of radiation searchlight materials.

[0026] Compared with the prior art, the present invention has the following advantages and beneficial effects:

[0027] 1. The present invention uses LaGdCaSrBaF 12 High entropy crystal is used as the scintillating crystal matrix material, Ce 3+ Ion doping into LaGdCaSrBaF 12 In the crystal lattice, since it is difficult to grow high entropy fluoride materials, the present invention successfully grows high entropy fluoride bulk single crystals which have never been reported so far.

[0028] 2. Ce:LaGdCaSrBaF prepared by the present invention 12 The high lattice distortion environment provided by the high entropy matrix in the high entropy crystal provides more energy wells for the formation of self-trapped excitons, making the energy transfer efficiency of self-trapped excitons to the luminescence center higher and the material scintillation performance better. The hysteresis diffusion effect caused by high entropy increases the radiation hardness of the material and can enhance the service life of the material.

[0029] 3. Ce:LaGdCaSrBaF prepared by the present invention 12 High entropy crystals have lower phonon energy and smaller 5d energy level splitting, which can greatly reduce Ce 3+ The probability of non-radiative transition of ion 5d energy level is reduced. In addition, disordered mixed crystals also regulate Ce at the atomic, molecular and group scales. 3+ The local coordination structure of ions makes it truly disordered. In addition, high entropy fluoride scintillating crystals can achieve shorter scintillation time and stronger radiation resistance. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 The fluorescence spectrum of the sample prepared in Example 1 excited by 280 nm light at room temperature;

[0031] Figure 2 This is the fluorescence lifetime spectrum corresponding to the 320nm emission peak of the sample prepared in Example 1 under 280nm light excitation. DETAILED DESCRIPTION

[0032] The specific implementation methods of the present invention are described in detail below through examples. These examples are implemented on the premise of the scheme described in the present invention, and provide detailed implementation methods and specific operating processes, but the protection scope of the present invention is not limited to the following examples.

[0033] The present invention is further described below in conjunction with the accompanying drawings and specific embodiments. Any features such as component models, material names, connection structures, preparation methods, materials, structures or composition ratios not clearly described in this technical solution are deemed to be common technical features disclosed in the prior art.

[0034] Example 1

[0035] This embodiment provides a LaGdCaSrBaF 12 The preparation method of the crystal includes the following steps:

[0036] Put 24.8232g LaF3, 27.1484g GdF3, 9.8925g CaF2, 15.9177g SrF2, 22.218g BaF2 and 1.0g PbF2 raw materials in a graphite crucible, grind them evenly, cover them with a lid, put them in a furnace and evacuate them to below 8Pa, then heat them up to 1350℃ at a rate of 300℃ / h, keep the temperature constant for 8 hours until the raw materials are completely melted and fully impurities are removed, then slowly cool them down at a rate of 1.5℃ / h for growth. After cooling to 150℃, that is, the growth is over, cool them down to room temperature at 30℃ / h, and then take out the crystal to obtain LaGdCaSrBaF 12 The crystal is recorded as pure LGCSB.

[0037] Figure 1 The fluorescence spectra of the five high entropy fluoride single crystal samples prepared in Examples 1 to 5 under 280nm excitation at room temperature are shown in the figure. As can be seen from the figure, there is energy transfer from gadolinium ions to cerium ions, and the luminescence peak of cerium ions red-shifts as the concentration of cerium ions increases.

[0038] Figure 2 The fluorescence lifetime spectra corresponding to the 320nm emission peak of four high entropy fluoride single crystal samples doped with cerium ions under 250nm light excitation. It can be seen that the photoluminescence decay time in the cerium-doped sample reaches an extremely fast 5.74ns, and the fast component accounts for 82.9%.

[0039] Table 1 shows the fluorescence decay time of four high entropy fluoride single crystal samples prepared in Examples 2-5 at room temperature. It can be seen from the table that the fluorescence decay time of the high entropy scintillator material is exponentially shorter than that of the general cerium-doped scintillator material, laying the foundation for high entropy scintillator materials.

[0040] Table 1. The fluorescence lifetime fitting statistics corresponding to the 320nm emission peak under 250nm light excitation

[0041]

[0042] Example 2

[0043] This embodiment provides a 0.5%Ce:LaGdCaSrBaF 12 The preparation method of the crystal includes the following steps:

[0044] Add 0.5% Ce ions in a molar mass ratio to the initial raw materials of 24.6685g LaF3, 26.979g GdF3, 9.8308g CaF2, 15.8185g SrF2, 22.0794g BaF2, 0.6236g CeF3 and 1.0g PbF2 with a purity of 5N to replace cations, grind and mix evenly. Put the weighed raw materials into a porous graphite crucible and cover it with a circular graphite cover with a diameter of 1mm. Evacuate the furnace and fill it with high-purity argon as a protective atmosphere. Heating at a rate of 320℃ / h to 2140℃, keep the temperature constant for 3 hours until the raw materials are completely melted, and slowly cool down at a rate of 1.5℃ / h for growth. After dropping to 150℃, that is, when the growth is over, drop to room temperature at 50℃ / h, and then take out the crystal. Obtain 0.5% Ce:LaGdCaSrBaF 12 Crystal.

[0045] Prepared 0.5%Ce:LaGdCaSrBaF 12 The crystal transmittance is greater than 80%, the fluorescence lifetime is 5.74ns, and the fast component accounts for 82.9%.

[0046] Example 3

[0047] This embodiment provides a 1.0%Ce:LaGdCaSrBaF 12The method for preparing the crystal is different from that in Example 2 in that, in this example, Ce ions with a molar mass ratio of 1.0% are added to the raw material single crystal particles of 24.5141g LaF3, 26.8102g GdF3, 9.7693g CaF2, 15.7194g SrF2, 21.9412g BaF2, 1.2457g CeF3 and 1.0g PbF2 with a purity of 5N to replace the cations, and the remaining steps are the same as those in Example 2 to obtain 1.0% Ce: LaGdCaSrBaF 12 Crystal.

[0048] Prepared 1.0%Ce:LaGdCaSrBaF 12 The crystal transmittance is greater than 80%, the fluorescence lifetime is 5.90ns, and the fast component accounts for 81.9%.

[0049] Example 4

[0050] This embodiment provides a 3.0%Ce:LaGdCaSrBaF 12 The method for preparing the crystal is different from that in Example 2 in that, in this embodiment, 3.0% Ce ions are added to the raw material single crystal particles of 23.9181g LaF3, 26.1584g GdF3, 9.5318g CaF2, 15.3373g SrF2, 21.4078g BaF2, 3.6463g CeF3 and 1.0g PbF2 with a purity of 5N to replace the cations, and the remaining steps are the same as those in Example 2 to obtain 3.0% Ce: LaGdCaSrBaF 12 Crystal.

[0051] Prepared 3.0%Ce:LaGdCaSrBaF 12 The crystal transmittance is greater than 80%, the fluorescence lifetime is 6.23ns, and the fast component accounts for 81.7%.

[0052] Example 5

[0053] This embodiment provides a LaCeCaSrBaF 12 The preparation method of the crystal includes the following steps:

[0054] 25.3743g LaF3, 25.531g CeF3, 10.1121g CaF2, 16.2711g SrF2, 22.7112g BaF2 and 1.0g PbF3 were placed in a graphite crucible, and the furnace was evacuated to below 8Pa. The temperature was raised to 1340℃ at a rate of 340℃ / h, and the temperature was kept constant for 8 hours until the raw materials were completely melted and the impurities were fully removed. Then the temperature was slowly lowered at a rate of 1.5℃ / h for growth. After the temperature was lowered to 150℃, that is, the growth was completed, the temperature was lowered to room temperature at 35℃ / h to obtain LaCeCaSrBaF with good optical quality. 12 Crystal, denoted as pure LCCSB.

[0055] The above description of the embodiments is to facilitate the understanding and use of the invention by those skilled in the art. It is obvious that those skilled in the art can easily make various modifications to these embodiments and apply the general principles described herein to other embodiments without creative work. Therefore, the present invention is not limited to the above embodiments, and improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the present invention should be within the scope of protection of the present invention.

Claims

1. A cerium ion doped high entropy fluoride scintillating crystal, characterized in that: The chemical formula of the scintillation crystal is Ce:M1M2CaSrBaF 12 , where M1 and M2 are any two of Y, Lu, Gd, La, Lu, Sc, and Ce; The space group of the scintillation crystal is Fm-3m (225), which belongs to the cubic crystal system.

2. The method for preparing a cerium ion-doped high entropy fluoride scintillating crystal according to claim 1, characterized in that: The chemical formula of the scintillation crystal is Ce:LaGdCaSrBaF 12 .

3. A method for preparing a cerium ion-doped high entropy fluoride scintillating crystal as claimed in claim 2, characterized in that: The following steps are involved: S1: Using single crystal particles or powders of LaF3, GdF3, CaF2, SrF2, BaF2 and CeF3 as raw materials, doping them with Ce ions, and grinding them evenly to obtain the matrix material; S2: The matrix material in S1 is loaded into a porous graphite crucible, and a lid is put on the crucible to prevent the large amount of volatilization of the raw materials, and the crucible is placed in a hot field and evacuated; S3: After the vacuum is evacuated, the power is turned on to increase the temperature and keep it warm for a period of time to ensure that the matrix material in S1 is completely melted and impurities are removed, and then the temperature is slowly lowered to grow the crystal. After the growth is completed, the temperature is lowered to room temperature to obtain a cerium-doped high-entropy fluoride scintillation crystal.

4. The method for preparing a cerium ion-doped high entropy fluoride scintillating crystal according to claim 3, characterized in that: In S1, the purity of the single crystal particles or powders of LaF3, GdF3, CaF2, SrF2, BaF2 and CeF3 is 5N.

5. The method for preparing a cerium ion-doped high entropy fluoride scintillating crystal according to claim 3, characterized in that: In S1, the grinding time is 40-60 min; In S1, the doping molar mass ratio of the Ce ions is 0.5%-3.0%.

6. The method for preparing a cerium ion-doped high entropy fluoride scintillating crystal according to claim 3, characterized in that: In S1, 1 wt. % of PbF2 is added to the matrix material, and the PbF2 serves as a deoxidizer to prevent the fluoride raw material from being oxidized.

7. The method for preparing a cerium ion-doped high entropy fluoride scintillating crystal according to claim 3, characterized in that: In S2, the vacuum is drawn to below 8 Pa.

8. The method for preparing a cerium ion-doped high entropy fluoride scintillating crystal according to claim 3, characterized in that: In S3, the heating rate is 100-200°C / h, the temperature is raised to 1350-1400°C, and the constant temperature time is 8-12h.

9. The method for preparing a cerium ion-doped high entropy fluoride scintillating crystal according to claim 3, characterized in that: In S3, the slow cooling rate is 1.5°C / h; In S3, the growth is terminated by slowly cooling the temperature to 150°C and then to room temperature at a cooling rate of 30-50°C / h.

10. An application of the cerium ion doped high entropy fluoride scintillation crystal as claimed in claim 1, characterized in that: The cerium ion doped high entropy fluoride scintillation crystal is used in the preparation of radiation search illumination materials.

Citation Information

Patent Citations

  • High-transmittance and high-entropy transparent ceramic and preparation method thereof

    CN111892400A

  • Rare earth ion doped disordered high-entropy fluoride ultrafast laser crystal and preparation method and application thereof

    CN116145254A

  • Spinel type high-entropy transparent ceramic as well as preparation method and application thereof

    CN117986004A

Cited By

  • High light yield fast response fluoride scintillator single crystal under high-energy excitation and preparation method thereof

    CN122707250A